Dual effect of ethanol on inward rectifier potassium current IK1 in rat ventricular myocytes - Bebarova, M; Matejovic, P; Pasek, M; Simurdova, M; Simurda, J (Journal of physiology and pharmacology, 2014)
Alcohol consumption may result in electrocardiographic changes and arrhythmias. Important role of modifications of the inward rectifier potassium current I(K1) in arrhythmogenesis is well established. Considering lack of relevant data, we aimed at studying the effect of 0.2-200 mM ethanol on I(K1) in enzymatically isolated rat right ventricular myocytes using the whole cell patch-clamp technique at 23±1°C. Ethanol reversibly affected I(K1) in a dual way. At a very low concentration of 0.8 mM (≈~0.004%), ethanol significantly decreased IK1 by 6.9±2.7%. However, at concentrations of ethanol ≥20 mM (≈0.09%), I(K1) was conversely significantly increased (by 16.6±4.0% at 20 mM and 24.5±2.4% at 80 mM). The steady-state I(K1) increase was regularly preceded by its transient decrease at the beginning of ethanol application. Under 2 and 8 mM ethanol, I(K1) was decreased at the steady-state in some cells but increased in others. Both effects were voltage-independent. In agreement with the observed effects of ethanol on I(K1), a transient action potential (AP) prolongation followed by its final shortening were observed after the application of ethanol in a low concentration of 8 mM (≈0.04%). Under the effect of 0.8 mM ethanol, only AP prolongation was apparent which agreed well with the above described I(K1) decrease. Other AP characteristics remained unaltered in both concentrations. These observations corresponded with the results of mathematical simulations in a model of the rat ventricular myocyte. To summarize, changes of the cardiac I(K1) under ethanol at concentrations relevant to the current alcohol consumption were first demonstrated in ventricular myocytes in this study. The observed dual ethanol effect suggests at least two underlying mechanisms that remain to be clarified. The ethanol-induced I(K1) changes might contribute to the reported alterations of cardiac electrophysiology related to alcohol consumption.
Keywords: potkani Wistar; kardiomyocyty; Heart Ventricles; akční potenciály; Potassium Channels, Inwardly Rectifying; Animals; ethanol; Ethanol; Myocytes, Cardiac; mužské pohlaví; draslíkové kanály dovnitř usměrňující; Male; Rats, Wistar; zvířata; Action Potentials; srdeční komory